2016
DOI: 10.1021/acs.orglett.6b02569
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Studies Clarify the Committed Step in Bacterial Gibberellin Biosynthesis

Abstract: Bacteria have evolved gibberellin phytohormone biosynthesis independently of plants and fungi. Through 13C-labeling and NMR analysis, the mechanistically unusual “B” ring contraction catalyzed by a cytochrome P450 (CYP114), which is the committed step in gibberellin biosynthesis, was shown to occur via oxidative extrusion of carbon-7 from ent-kaurenoic acid in bacteria. This is identical to the convergently evolved chemical transformation in plants and fungi, suggesting a common semipinacol rearrangement mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Notably, unlike recombinantly expressed CYP114+Fd GA from other bacteria, including those from X. hydroxykaurenoic acid to a similar mixture of GA 12 -aldehyde and lesser amounts of GA 12 (Supplemental Figure S4B). Consistent with previous work on the CYP114+Fd GA from the α-rhizobia S. fredii (Nett et al, 2016), trace amounts of ent -6α,7α-dihydroxykaurenoic acid was observed here, but neither this (Supplemental Figure S4C+B), nor the closely related kaurenolide or 7β-hydroxykaurenolide (neither of which were observed here) appeared to be further transformed by Et CYP114+ Et Fd GA (data not shown).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, unlike recombinantly expressed CYP114+Fd GA from other bacteria, including those from X. hydroxykaurenoic acid to a similar mixture of GA 12 -aldehyde and lesser amounts of GA 12 (Supplemental Figure S4B). Consistent with previous work on the CYP114+Fd GA from the α-rhizobia S. fredii (Nett et al, 2016), trace amounts of ent -6α,7α-dihydroxykaurenoic acid was observed here, but neither this (Supplemental Figure S4C+B), nor the closely related kaurenolide or 7β-hydroxykaurenolide (neither of which were observed here) appeared to be further transformed by Et CYP114+ Et Fd GA (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…This enabled demonstration of the specific production of GGDP by the associated IDSs, rather than a mixture of different chain length products as seen with other such enzymes (Schmidt et al, 2010; Nagel et al, 2015), which is consistent with dedicated production of the derived GAs. In addition, the ability of Et CYP114+ Et Fd GA to convert ent -7α-hydroxykaurenoic acid to GA 12 -aldehyde further supports the relevance of this intermediate, consistent with recent labeling experiments (Nett et al, 2016). …”
Section: Discussionsupporting
confidence: 86%
“…Both constructs were expressed in E. coli and ent -kaurenoic acid was added to the resulting cultures. Cultures expressing Pm CYP114 + Pm Fd (i.e., without the SDR) produced a mixture of GA 12 -aldehyde and GA 12 , while the Pm CYP114 + Pm Fd-SDR construct exclusively produced GA 12 , with the putative intermediate ent -7α-hydroxykaurenoic acid not observed in either case (Figure 4 and Supplementary Figure S1 ), consistent with previous mechanistic investigation of this reaction ( Nett et al, 2016 ). This demonstrated the ability of the Fd to enable full CYP114 activity as a fusion protein with the SDR, as well as the expected more efficient oxidation of GA 12 -aldehyde to GA 12 by the SDR.…”
Section: Resultssupporting
confidence: 88%
“…Oxidation with ring contraction to GA 12 aldehyde (41) by CYP114 proceeds with specific extrusion of C-7, as demonstrated by a 13 C-labelling experiment through feeding with (2-13 C)mevalonolactone. [58] This step is followed by an oxidation to GA 12 (42)b yS DR GA .T he final oxidations to GA 15 (43), GA 24 (44), and GA 9 (45)a re performed by CYP112. [57] Notably,t he identified pathway intermediates and reactions are essentially the same as in plants and fungi, but the responsible enzymes are completely unrelated in all three cases,thus giving an interesting example of convergent evolution.…”
Section: Ent-copalyl Diphosphate Synthasementioning
confidence: 99%